2014
DOI: 10.1155/2014/797681
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metformin in Metabolic Disturbances during Pregnancy: Polycystic Ovary Syndrome and Gestational Diabetes Mellitus

Abstract: Maintenance of gestation implicates complex function of multiple endocrine mechanisms, and disruptions of the global metabolic environment prompt profound consequences on fetomaternal well-being during pregnancy and postpartum. Polycystic Ovary Syndrome (PCOS) and gestational diabetes mellitus (GDM) are very frequent conditions which increase risk for pregnancy complications, including early pregnancy loss, pregnancy-induced hypertensive disorders, and preterm labor, among many others. Insulin resistance (IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 166 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…In recent years, MF therapy has become widely used for correction of the metabolic and hormonal impairments in women with PCOS and for restoration of their reproductive functions [ 85 , 108 , 109 , 110 ], including the improvement of IVF/ICSI outcomes in PCOS [ 111 , 112 , 113 , 114 ]. MF is most effective in treating PCOS patients with the metabolic disorders such as T2DM, obesity, dyslipidemia, and severe IR [ 85 , 115 , 116 ]. This is majorly attributed to the alleviation of negative effects of these disorders on the female reproduction by MF, increased tissues sensitivity to insulin, improved lipid and glucose metabolism and cell metabolism, and reduced inflammation and oxidative stress in the ovaries as well as in other tissues.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…In recent years, MF therapy has become widely used for correction of the metabolic and hormonal impairments in women with PCOS and for restoration of their reproductive functions [ 85 , 108 , 109 , 110 ], including the improvement of IVF/ICSI outcomes in PCOS [ 111 , 112 , 113 , 114 ]. MF is most effective in treating PCOS patients with the metabolic disorders such as T2DM, obesity, dyslipidemia, and severe IR [ 85 , 115 , 116 ]. This is majorly attributed to the alleviation of negative effects of these disorders on the female reproduction by MF, increased tissues sensitivity to insulin, improved lipid and glucose metabolism and cell metabolism, and reduced inflammation and oxidative stress in the ovaries as well as in other tissues.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…Available animal studies suggest that metformin does not have teratogenic or carcinogenic effects even at very high doses of 600–1500 mg/kg/day [ 85 ]. A Brazilian group demonstrated that metformin had the potential to cause deoxyribonucleic acid (DNA) damage in vitro in cells of Chinese Hamster ovary (CHO-K1), but not in vivo in mice [ 86 ].…”
Section: Concerns With Fetal Exposure To Metforminmentioning
confidence: 99%
“…In the last few years, two stereoisomers of inositol, myo-inositol (MI) and D-chiro-inositol (DCI) have attracted scientific interest and related research on them has gained momentum. MI and DCI are cyclic polyols (C 6 H 12 O 6 ) with MW 180.16, present in all living forms; they are involved in a wide array of metabolic pathways with significant therapeutic applications in pathologies (e.g., PCOS, GDM, MetSyn) where insulin sensitizing agents play a key role [ 4 , 6 , 7 ]. Obviously, they are even more useful as they do not involve significantly adverse events [ 8 ].…”
Section: Introductionmentioning
confidence: 99%